2016
DOI: 10.1038/srep32040
|View full text |Cite
|
Sign up to set email alerts
|

Ice VII from aqueous salt solutions: From a glass to a crystal with broken H-bonds

Abstract: It has been known for decades that certain aqueous salt solutions of LiCl and LiBr readily form glasses when cooled to below ≈160 K. This fact has recently been exploited to produce a « salty » high-pressure ice form: When the glass is compressed at low temperatures to pressures higher than 4 GPa and subsequently warmed, it crystallizes into ice VII with the ionic species trapped inside the ice lattice. Here we report the extreme limit of salt incorporation into ice VII, using high pressure neutron diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 32 publications
0
43
0
Order By: Relevance
“…1 This behaviour contrasts with the one observed in LiX solutions close to the eutectic composition (LiClÁ6D 2 O and LiBrÁ5.5D 2 O) where an abrupt increase in the Li + ion coordination was observed when following the same thermodynamic path. 3 Combining the results of molecular dynamics simulations based on classical polarisable potentials 4,5 and neutron diffraction experiments, 6 we have shown that the behaviour of such solutions upon compression is essentially driven by the structure of the hydration shells of the respective cation. 1 The first neighbours' shell of Li + has a tetrahedral structure at ambient pressure, which breaks up near 2 gigapascal to form an octahedral shell, giving rise to the observed sudden change in density.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 This behaviour contrasts with the one observed in LiX solutions close to the eutectic composition (LiClÁ6D 2 O and LiBrÁ5.5D 2 O) where an abrupt increase in the Li + ion coordination was observed when following the same thermodynamic path. 3 Combining the results of molecular dynamics simulations based on classical polarisable potentials 4,5 and neutron diffraction experiments, 6 we have shown that the behaviour of such solutions upon compression is essentially driven by the structure of the hydration shells of the respective cation. 1 The first neighbours' shell of Li + has a tetrahedral structure at ambient pressure, which breaks up near 2 gigapascal to form an octahedral shell, giving rise to the observed sudden change in density.…”
mentioning
confidence: 99%
“…This process explains the gradual densification observed in the NaClÁ10.2D 2 O system. 1 We have shown that in the case of LiCl and LiBr solutions 6,7 such high-density amorphous structures act as precursors for a crystalline ice phase which is formed upon further annealing of the temperature under pressure. The structure of this salty ice closely resembles the one of pure ice VII but large amounts of Li + , Br À and Cl À ions are included in the lattice, either interstitially (Li + ) in octahedral voids or by substituting water molecules on sites of the ice VII lattice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the system size of computer simulations is getting larger and larger, and there is a great need for preparing many hydrogen bond networks of different orderliness efficiently. GenIce has already been used in our researches,16, 30, 31, 32, 33, 34 and we will continue to improve the tool to generate more complex structures such as ice including various types of defects which play important roles in dynamic properties 35…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the sample pressure can be changed even at low temperatures. This system is applied to the study of ice under low-T and high-P conditions [89,90]. PLANET is widely used in the fields of geoscience, high-pressure physics, and material science.…”
Section: High-pressure Neutron Diffractometer Planetmentioning
confidence: 99%